(untitled) (Bioagro, 2021)
Plant-parasitic nematodes cause 14 % of annual losses in different crops in the world and there are more than 35 genera of phytoparasitic nematodes associated with the rhizosphere of the papaya crop (Carica spp.), being the most important the root-knot nematode (Meloidogyne spp). The present study aimed to carry out the morphological identification of the genera of nematodes associated with the cultivation of Andean papaya (Carica pubescens), in Sandia district, Puno, Perú. One-hundred and fifty-five soil and roots samples from eight communities were evaluated. The samples were processed by the centrifugal fluctuation method in sucrose solution and subsequent identification of the nematodes at the genus level, using the dichotomous key of Mai and Mullin. We found the genus Meloidogyne, Pratylenchus, Helicotylenchus, Mesocriconema, Apelenchus, Dorilaymus, Tylenchus, Xiphinema, Mononchus, Discocriconemella, Trichodorus and other unidentified free-living nematodes. This information may allow the design of an integrated nematode management plan in Andean papaya crops.